Effects of vardenafil on the kidney of Wistar rats submitted to acute ischemia and reperfusion - Sousa,Renato Chavasco de (2015)
PURPOSE: To investigate the effect of vardenafil in kidney of rats submitted to acute ischemia and reperfusion.METHODS:Twenty-eight rats were randomly distributed into two groups. Right nephrectomy was performed and the vardenafil group received vardenafil solution (at a concentration of 1 mg/ml in 10 mg/kg) while the control group received 0.9% saline solution (SS) one hour prior to the ligature of the left renal pedicle. After one hour of ischemia, animals were submitted to twenty-four hours of reperfusion, followed by left nephrectomy. The kidney's histological parameters evaluated on the study included vacuolar degeneration and tubular necrosis. Apoptosis was assessed by immunohistochemistry for cleaved caspase-3 using the point-counting and digital methods (Cytophotometry). Also, a biochemical analysis for creatinine was conducted.RESULTS: There were statistically significant differences between groups only with regards to the vacuolar degeneration parameter and to the cleaved caspase-3 digital method.CONCLUSION: Vardenafil showed a protective effect on the kidney of rats subjected to acute ischemia and reperfusion in this model